Report of the Special U.S. Economic Mission to Nigeria - Rivkin, Arnold; United States. Special Economic Mission to Nigeria (Washington, D.C., 1961)
This report was presented to the President's Task Force on Foreign Economic Assistance, the Department of State, and the International Cooperative Administration on the Special U.S. Economic Mission to Nigeria
Report presented to the President's Task Force on Foreign Economic Assistance.
rpm 19/04/2017
Loans
Keywords: Nigeria -- Economic conditions -- 1960-; Nigeria -- Economic policy; Economic assistance, American -- Nigeria; Economic assistance, American; Economic history; Economic policy; Nigeria